TINJAUAN YURIDIS KEWENANGAN PENERIMAAN PEGAWAI BARU OLEH PIMPINAN BNI (Persero, Tbk) KANTOR WILAYAH PEMUDA MEDAN - BOY SINAGA (PREMISE LAW JURNAL, 2017)
ABSTRACT As the incumbent leader who gained the trust of stakeholders, shareholders to carry out the duties and responsibilitieshis responsibility. Relationship between stareholders, shareholders and the CEO is based on the Doctrine of Fiduciary Duty,this is why leadership of PT BNI (Persero Tbk) must carry out their duties and responsibilities to carry out the implementation of Good Corporate Governance (GCG). Transparency, accountability, responsibility, independence, fairness with regard to the ethics and rules. Good Corporate Governance (GCG), the following provisions of Regulation No : 8/4 years of 2006 and amendment No. 8/14 years 2006 and BI regulation No. 8/4 year 2006 leadership of PT Bank Negara Indonesia Persero, Tbk. Kanwil Medan, have a responsibility to do good authority by applying the principles of Good Corporate Governance (GCG). recruitment In case, the implementation of new recruitment in accordance with the principles of Good Corporate Governance (GCG). Claiming that the incumbent leadership has implemented good Doctrine of Fiduciary Duty by responsible leaders in recruitment is not infinite but limited by the Principles of Good Corporate Governance (GCG). PT Bank Negara Indonesia Medan Youth as a limited liability company, also doing business under the Act limited liability company no: 40 of2007. Leaders must provide equal opportunities in recruitment and career Profesiaonal carrying out their duties. Transparency is openness in the decision making process in terms of ^recruitment. Accountability is a function of clarity, implementation and leadership accountability over hiring decisions. Responsibility is the suitability of the application of the .principles of Good Corporate Governance (GCG). In carrying Fiduracy doctrine Duty to hiring. Independence is a condition in which the management of the authority in terms of recruitment is done professionally without any conflict of interest and influence / pressure 'from any party which is not in accordance with the legislation in force and the principles of Good Corporate Governance (GCG). Fairness is fairness and equality in meeting the stake holders rights arising under the agreement and the rules that apply keyword: leadership fiduciary Duty of Good Corporate Governance (GCG), personnel recruitment Keyword : Leader, management of authority, fiduracy